2022
DOI: 10.3389/fncir.2022.784280
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 30 Minutes of Artificial Gravity on Cognitive and Sensorimotor Performance in a Spaceflight Analog Environment

Abstract: The altered vestibular signaling and somatosensory unloading of microgravity result in sensory reweighting and adaptation to conflicting sensory inputs. Aftereffects of these adaptive changes are evident postflight as impairments in behaviors such as balance and gait. Microgravity also induces fluid shifts toward the head and an upward shift of the brain within the skull; these changes are well-replicated in strict head-down tilt bed rest (HDBR), a spaceflight analog environment. Artificial gravity (AG) is a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 76 publications
3
43
0
Order By: Relevance
“…De Martino et al (2021) analyzed the effects of AG on upright balance, finding that intermittent AG partially mitigated balance impairment from pre to post-HDBR compared to CTRLs, but continuous AG did not differ from CTRLs. This finding is somewhat in line with our own previous findings that AG may be beneficial for balance (Tays et al, 2022). We have also recently reported effects of AG on cognitive function, showing that during centrifugation there was an increased level of cognitive ability compared to controls, as measured by the Paced Auditory Serial Addition Task (PASAT; Tays et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…De Martino et al (2021) analyzed the effects of AG on upright balance, finding that intermittent AG partially mitigated balance impairment from pre to post-HDBR compared to CTRLs, but continuous AG did not differ from CTRLs. This finding is somewhat in line with our own previous findings that AG may be beneficial for balance (Tays et al, 2022). We have also recently reported effects of AG on cognitive function, showing that during centrifugation there was an increased level of cognitive ability compared to controls, as measured by the Paced Auditory Serial Addition Task (PASAT; Tays et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is somewhat in line with our own previous findings that AG may be beneficial for balance (Tays et al, 2022). We have also recently reported effects of AG on cognitive function, showing that during centrifugation there was an increased level of cognitive ability compared to controls, as measured by the Paced Auditory Serial Addition Task (PASAT; Tays et al, 2022). Basner et al, (2022) found that HDBR overall had a negative effect on cognitive performance, and that receiving AG did not mitigate these declines.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations